Intra-population variation in the diet of an avian top predator: generalist and specialist foraging in Great Black-backed Gulls Larus marinus. Issue 3 (3rd July 2019) - Westerberg, Katherine; Brown, Richard; Eagle, Giselle; Votier, Stephen C.
ABSTRACT: Capsule: Great Black-backed Gulls Larus marinus breeding on Skokholm, UK, fed predominantly on seabirds, rabbits, refuse, and marine prey, with the majority of pairs being dietary generalists, but with some specialist pairs. Aims: To understand the significance of Great Black-backed Gulls as top predators on a small offshore island with internationally important numbers of breeding seabirds (Skokholm, UK) by quantifying their diet and to determine how this varies within the breeding season, to test for pair-level dietary specialization and to examine the consequences of dietary differences for reproductive performance. Methods: Regurgitated pellets were collected and analysed from 26 breeding pairs on Skokholm during 2017 and related to breeding success. Results: Analysis of 1035 pellets revealed that, overall, Great Black-backed Gulls fed on seabirds (48% – mostly Manx Shearwaters Puffinus puffinus ), mammals (38% – mostly European Rabbits Oryctolagus cuniculus ), anthropogenic waste (7%), and marine prey (7%). Diet varied among pairs with 18 (73%) generalist pairs and 7 (27%) specialist pairs (of which, 5 were bird specialists and 2 were mammal specialists). Diet also varied seasonally, but pair-level dietary diversity was repeatable through the breeding season. Dietary diversity did not covary with breeding success. Conclusion: Great Black-backed Gulls are top predators on Skokholm. Variation in diet among pairs emphasizes that not all individuals contribute equally in terms of predation. Understanding the incidence of this variation has important ecological implications, particularly where apex predators may exert a strong top-down influence.